PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN JASA SIMPAN PINJAM PADA KUD SUMBER MAKMUR KECAMATAN TANJUNG KABUPATEN BREBES - Rahayu, Sri; Handayani, Sri Ratih (PERMANA, 2014)
This research is about influence of quality of service to decision of client to use saving and loan service [at] KUD Sumber Makmur Sub-Province of Brebes. Target of research to know influence of quality of service to decision of client to use saving and loan service and to know how big influence of quality of service to decision of client to use saving and loan service [at] KUD Sumber Makmur Sub-Province of Brebes. Pursuant to result of calculation of correlation coefficient [among/between] quality of service and decision of client obtained [by] correlation coefficient equal to 0,912. Matter this means that [relation/link] [among/between] quality of service with decision of client [is] positive and big because level of correlation coefficient [is] to come near 1 (one). Strength and positive of quality of service and decision of client can be proved with simple correlation coefficient significance test [at] trust storey;level 95 [gratuity/ %] and degree of freedom (100-2) obtained [by] ttabel equal to 1,6609 and thitung equal to 22,011. Because thitung > ttabel hence Ho refused and [Is] Ha accepted with the meaning that there are correlation which [is] signifikan [among/between] quality of service with decision of client. While equation of simple regresi the obtained [is] Y=-0,486+1,009X, meaning that decision of client to use saving and loan service [in] KUD Sumber Makmur will be downhill if given service [do] not with quality conversely decision of excelsior client to use saving and loan service [in] KUD Sumber Makmur given service with quality or there [is] make-up of the quality of service.